SOEP-Core - 2020: Sampling, nonresponse, and weighting in living in Germany - Nationwide Corona Monitoring (RKI-SOEP) - Hans Walter Steinhauer; Sabine Zinn; Rainer Siegers (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
In autumn 2020, the Robert Koch Institute (RKI) joined forces with the Socio-Economic Panel (SOEP) to launch the study "Living in Germany-Corona Monitoring" on the prevalence of current and past SARS-CoV-2 infections in a sample of the adult population in Germany. The survey began shortly thereafter, in October 2020. Participation was voluntary and entailed completion of a questionnaire on COVID-19 infections and symptoms, testing, and health behavior, as well as self-administered tests for current COVID-19 infections (PCR test) and antibodies (DBS test). The results allow for estimation of seroprevalence in the population and identification of socio-economic differences in infection rates and health behavior. Because the study covers all adults in each participating household, it increases the potential for analysis. Selectivity is likely to occur on the household and individual level and may bias results. Here, the use of information from an ongoing panel allowed us to analyze and adjust for possible selectivities due to noncontact, attrition, and refusal at both levels. At the household level, we find characteristics related to the spread of COVID-19 as well as health-related variables to be the main drivers of noncontact, attrition, and refusal. At the individual level, we find age and household composition to be the main drivers of attrition and refusal.
Keywords: 330